The Relation Between Nutritional Status and Healing Time for Patients Undergoing Hematopoietic Stem Cells Transplantation Sample - Weheida, Soheir; Badry, Salwa El-; Rizk, Asmaa (International Journal For Research In Health Sciences And Nursing, 2018)
Background: Hematopoietic stem cell transplantation is considered a lifesaving procedure for many hematologic and non-hematologic malignancies. Multiple factors affect transplantation outcome as nutritional status of the patient either over nourished or undernourished. Malnutrition prior to transplant has been reported as a negative prognostic factor following Hematopoietic stem cell transplantation. A recent meta-analysis confirmed that obese recipient has increased risk of acute graft versus host disease and may have increased mortality rates. Aim: Determine the relation between nutritional status and healing time for patients undergoing hematopoietic stem cell transplantation. The study was conducted at Al Mouwasat University Hospital, Alexandria University and Nasser Institute Hospital, Cairo. Subjects: The study was conducted on a purposive sample of 40 patients who necessitate hematopoietic stem cell transplantation. Tools: Two tools were used. Tool I: Socio demographic and clinical data of patients submitted to hematopoietic stem cells transplantation, structured interview schedule and Tool II: Patient’s nutritional assessment record prior to hematopoietic stem cells transplantation. Results: The three quarters of patients were either overweight or obese pre transplantation, the underweight patients had the longest engraftment time and longest hospitalization, and it was observed that the more the body mass index (BMI) and body fat percent, the less time for engraftment. Conclusion and Recommendations: it is necessary to initiate nutritional assessment and follow up for those patients to prevent malnutrition and to protect the borderline patients to become negatively malnourished and consequently affecting healing time negatively. Moreover, despite the obesity is a risk factor for graft versus host disease and transplantation complications, it is not dangerous as malnutrition in occurrence of late engraftment.